2002
DOI: 10.1002/cne.10455
|View full text |Cite
|
Sign up to set email alerts
|

Descending spinal projections from the rostral gigantocellular reticular nuclei complex

Abstract: Electrophysiological and physiological studies have suggested that the ventral medullary gigantocellular reticular nuclei (composed of the gigantocellular ventralis and pars alpha nuclei as well as the adjacent lateral paragigantocellular nucleus; abbreviated Gi-LPGi complex) provide descending control of pelvic floor organs (Mackel [1979] J. Physiol. (Lond.) 294:105-122; Hubscher and Johnson [1996] J. Neurophysiol. 76:2474-2482; Hubscher and Johnson [1999] J. Neurophysiol. 82:1381-1389; Johnson and Hubscher [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 85 publications
2
29
0
Order By: Relevance
“…Penile afferents project to the paragigantocellularis region of the medial reticular formation (20), and afferents activated by DNP stimulation, urethral infusion, and bladder distension converge on neurons in the medullary reticular formation (26). The ventral medullary gigantocellular reticular nuclei (which consists partially of the lateral paragigantocellular nucleus) projects to the intermediate gray and sacral parasympathetic nucleus of the sacral spinal cord (23). The convergence of penile somatic and bladder parasympathetic pathways is not surprising considering that DNP afferents and parasympathetic efferents are involved in erectile function (43).…”
Section: Discussionmentioning
confidence: 99%
“…Penile afferents project to the paragigantocellularis region of the medial reticular formation (20), and afferents activated by DNP stimulation, urethral infusion, and bladder distension converge on neurons in the medullary reticular formation (26). The ventral medullary gigantocellular reticular nuclei (which consists partially of the lateral paragigantocellular nucleus) projects to the intermediate gray and sacral parasympathetic nucleus of the sacral spinal cord (23). The convergence of penile somatic and bladder parasympathetic pathways is not surprising considering that DNP afferents and parasympathetic efferents are involved in erectile function (43).…”
Section: Discussionmentioning
confidence: 99%
“…Descending projections from the nPGi to spinal cell groups outside of those devoted to the somatic component of genital reflexes have been noted, including the intermediolateral cell column and the sacral parasympathetic nucleus (Holstege et al, 1979;Hermann et al, 2003). In addition, the nPGi projects to the LC in rats (Aston-Jones et al, 1986;Luppi et al, 1995), and this nPGi-LC pathway has been implicated in a number of arousal-dependent functions (Chen and Engberg, 1989;Clark and Proudfit, 1991;Clayton and Williams, 2000).…”
Section: The Npgi As a Central Integrator For Arousalmentioning
confidence: 96%
“…Projections from the nPGi terminate onto the spinal motor neurons that innervate the bulbospongiosus and ischiocavernosus muscles (Tang et al, 1999;Murphy and Marson, 2000;Hermann et al, 2003); these muscles are critical to the control of erection and ejaculation (McKenna and Nadelhaft, 1986;Holmes et al, 1991). Bilateral lesions of the nPGi in male rats decrease mount and intromission frequency, as well as ejaculation latency, and increase the number of ejaculations to satiety (Yells et al, 1992(Yells et al, , 1994.…”
mentioning
confidence: 97%
“…Moreover, these findings fit with the idea that spinal genitourinary circuits are under inhibitory control of supraspinal brainstem structures presumably mediated by 5-HT. [24][25][26] Effects of SSRIs on ejaculation in humans The frequently reported sexual side effects of SSRIs in men suggest an important role of 5-HT in human ejaculatory behavior. 27 As described previously, in several human studies, we and others have demonstrated that various SSRIs such as paroxetine, sertraline and fluoxetine are able to delay ejaculation in men with premature ejaculation.…”
Section: Serotonin Serotonergic Receptors and Ejaculatory Behaviormentioning
confidence: 99%